Layered Architecture Consistency for MANETs: Introducing New Team Members - Padberg, Julia; Biermann, Enrico; Hoffmann, Kathrin (Electronic Communications of the EASST, 2009)
In this paper we extend our results concerning the layered architecture for modeling workflows in Mobile Ad-Hoc networks (MANETs) using algebraic higher order nets. MANETs are networks of mobile devices that communicate with each other via wireless links without relying on an underlying infrastructure. Workflows in can be adequately modeled using a layered architecture, where the overall workflow, the team members’ activities and the mobility issues are separated into three different layers, namely the workflow layer, the mobility layer and the team layer. In fromer papers a formal notion of layer consistency was suggested, that we now extend to allow changes of the interfaces of the gluing of the workflow and the mobility layer.